"Comment les femmes ordinairement appetent choses defendues": writing women into the history of Rabelais' reception (1628-1785) - Tolley, O (2019)
This thesis makes three key contributions to early modern French studies; it reintroduces forgotten perspectives into the history of Rabelais’ reception, offers new, less phallocentric, ways of reading the major episodes in Rabelais’ work that feature questions of women and femininity, and reconsiders early modern processes of authorial construction and posterity more generally. Women readers and audiences have thus far been excluded from the history of Rabelais’ afterlives. This study addresses this gap in scholarship by exploring a diverse range of thus far neglected seventeenth and eighteenth-century re-appropriations of Rabelais’ work. These sources take the form of literary genres associated with feminine culture in the early modern world: ballets, anecdotes, letters, journals and illustrations. I consider the ways in which these moments not only complicate the critical narrative of Rabelais’ literary afterlives but also help us to reread those episodes of Rabelais’ work that have proved to be the most problematic when it comes to the issue of women in Rabelais’ world. Through detailed analysis of these instances of re-appropriation in conjunction with close readings of Rabelais’ primary text, I make the case for a feminist reading of Rabelais’ work whereby the woman reader may take linguistic pleasure in the text. I debunk the current critical characterisation of Rabelais’ text as masculinist by demonstrating the extent to which the misogyny of the text is a fabrication of posterity related to the narratives surrounding Rabelais’ life, rather than an aspect inherent to the work itself. Despite the important contributions to Rabelais studies made by queer criticism in recent years, this work has thus far been predominantly phallocentric in nature. My thesis readdresses this imbalance, offering a more balanced approach to reading gender in Rabelais’ text. I suggest that the figure of ‘Dame mouche’ provides a useful model for thinking about what it means to read Rabelais’ work as a woman. By underlining the ways in which re-appropriations of texts and constructions of authorial personas serve to both include and exclude, this thesis reveals the gendered and class-based power structures that shape a writer’s posterity. By taking more seriously the lessons of reception history, this study distinguishes Rabelais’ work from the mythmaking surrounding the author’s life, and offers a fresh perspective on reading Rabelais’ women.